Cerebrospinal fluid and serum d-serine concentrations are unaltered across the whole clinical spectrum of Alzheimer's disease - Nuzzo, Tommaso; Miroballo, Mattia; Casamassa, Alessia; Mancini, Andrea; Gaetani, Lorenzo; Nisticò, Robert; Eusebi, Paolo; Katane, Masumi; Homma, Hiroshi; Calabresi, Paolo; Errico, Francesco; Parnetti, Lucilla; et al. (Biochimica et biophysica acta. Proteins and proteomics, 2020)
The diagnosis of Alzheimer's disease (AD) relies on the presence of amyloidosis and tauopathy, as reflected in cerebrospinal fluid (CSF), independently from the clinical stage. Recently, CSF d-serine has been proposed as a possible new AD biomarker, reflecting dysfunctional activation of neuronal glutamatergic N-methyl-d-aspartate receptor (NMDAR). In this study, we measured blood serum and CSF concentration of two NMDAR modulators, such as d-serine and d-aspartate, in a cohort of drug-free subjects encompassing the whole AD clinical spectrum. In addition, we also analyzed d-serine levels in a cohort of post-mortem AD and control cortex samples. We reported unaltered serum and CSF concentrations of d-serine and d-aspartate in AD patients both during the AD progression and compared to non-demented controls. Accordingly, no correlation was detected between serum or CSF d-serine content and mini-mental state examination or Clinical Dementia Rating. Similarly, cortical d-serine levels were also unaltered in post-mortem samples of AD patients. Overall, our results failed to confirm previous findings indicating the CSF d-serine as a novel biomarker for AD. •CSF d-serine has been proposed as possible new Alzheimer's Disease (AD) biomarker.•CSF and serum content of d-serine were unaltered in Alzheimer's Disease patients.•No correlation was found between CSF d-serine and MMSE or CDR scores.•Our study does not confirm CSF d-serine as a novel biomarker for AD.